IWISH: A HOUSING-BASED SERVICE COORDINATOR/NURSE TEAM MODEL TO HELP LOW-INCOME ELDERLY RESIDENTS “AGE IN PLACE” - Stone, R I (Innov Aging, 2018)
The Integrated Wellness in Supportive Housing (IWISH) program, a $15 million randomized control trial supported by the U.S. Department of Housing & Urban Development, tests the impact of a service coordinator/community nurse manager team embedded in 40 subsidized older adult housing sites. Working with residents, the team develops healthy aging plans and partners with local health and social services organizations to reduce unnecessary hospitalizations, emergency department visits and transfers to nursing homes and improve the health and quality of life of low-income elderly residents. This presentation describes the development of this new demonstration, highlighting the steps involved in early implementation, the challenges to successfully rolling out this “real world” intervention and how the implementation team worked together with its federal and private sector partners to achieve early successes. The presentation concludes with a summary of IWISH’s potential for influencing policy around new models of service delivery to Medicare beneficiaries.